1995
DOI: 10.1111/1467-9566.ep10932690
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in health: the interaction of circumstances and health related behaviour

Abstract: This paper derives its main hypothesis from results of the Health and Lifestyle Survey as reported in Blaxter's monograph Health and Lifestyles. In this book it is argued that in a favourable social environment a healthy lifestyle matters but in a unfavourable social environment a healthy lifestyle does not make much difference. This hypothesis is tested with data from health surveys from the Netherlands and Denmark. The Dutch data showed a highly significant relationship of unfavourable material and social ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Blaxter [11], using data from the same survey, found that healthy behaviour has a strong influence on health in 'favourable' circumstances (such as higher social class) but little influence in 'unfavourable' circumstances. Kooiker and Christiansen [12] found little evidence of this effect in Dutch and Danish health surveys. Further empirical estimation of the difference in health response to changes in income, social class, education etc.…”
Section: Implications For Future Researchmentioning
confidence: 97%
“…Blaxter [11], using data from the same survey, found that healthy behaviour has a strong influence on health in 'favourable' circumstances (such as higher social class) but little influence in 'unfavourable' circumstances. Kooiker and Christiansen [12] found little evidence of this effect in Dutch and Danish health surveys. Further empirical estimation of the difference in health response to changes in income, social class, education etc.…”
Section: Implications For Future Researchmentioning
confidence: 97%
“…Since health status is often affected by people's lifestyle (Blaxter, 1990;Gesler, 1992;Galaty & Johnson, 1990;Hertzel & McMichael, 1989;Kooiker & Christiansen, 1995) as well as social and natural environments (Foggin et al, 2001;May, Cancer of the womb was also a self-reported disease and will include other benign tumours and abdominal conditions. 1994; McCray, 2004;Perz, 1997), questions were also asked about these categories of risk factor.…”
Section: Lifestyle and Environmental Factorsmentioning
confidence: 99%
“…Another key premise of a determinants of health perspective is that health care provided by physicians and other health care professionals is only one of many factors that influence health. Health is also influenced by a broad range of community-based services, supports and programs, and by relationships between and among people's personal health practices and coping skills, living and working conditions, and socio-economic, political, and physical environmental contexts [15,17,[46][47][48][49][50][52][53][54][55]. Accordingly, a determinants of health perspective casts our attention beyond the narrow range of health care services that low-income Canadians use when they are ill to a broad range of services, supports, and programs that they use to maintain and promote their health-what we refer to as health-related services.…”
Section: Introductionmentioning
confidence: 99%